Theoretical Study on Meshing Stiffness of Cycloid-pin Gear Drive based on Energy Method - Yang Yun; Li Chaoyang; Li Xuan (Jixie chuandong)
Based on energy method and Hertz contact theory,a calculation model of mesh stiffness of the cycloid-pin gear pair is proposed with considering the bending,shearing and compression deformation of the cycloid gear tooth as well as the bending,shearing deformation of the pin. With calculating the torsion deformation of cycloid gear under load condition,the calculation formula of mesh stiffness and torsional stiffness of single tooth pair at the contact point are given. Based on the proposed calculation model,the influence of tooth profile parameters on the meshing stiffness and torsional stiffness are analyzed,including the eccentricity,pin position radius,pin radius and tooth number. The calculation method can be used for the analysis of the force and dynamics characteristic of the cycloid-pin gear drive,it has a certain reference value.